A search for novel genes that govern dendritic pruning in drosophila sensory neurons, ddaC during its metamorphosis - Koh, Yong Hui (2014)
Pruning, a refinement process in neuronal remodelling, has an essential role in the maturation of the nervous system in normal development. It is one of unique and economical way the nervous system has adopted to remove its exuberant branches without undergoing cell death. In recent decades, with the development of scientific techniques, it has shed some lights into the molecular mechanisms of pruning; uncovering some key transcriptional regulators that govern this refinement process. In this paper, mosaic analysis with a repressible cell marker (MARCM) technique was used to screen for additional novel genes that may be involve in this process. There were 3 positive lines identified. A line denoted as FK-02-32 was further characterized by immunostaining for Ubiquitin (Ub), Ecdysone receptor isoform B1 (EcR-B1) and Molecule interacting with casL (Mical). We showed that this line does not have defect in the ubiquin-proteasome system (UPS) and is not a regulator for EcR-B1 and Mical in the ecdysone signalling pathway. However, future investigation is required to establish its role in governing dendritic pruning during Drosophila’s metamorphosis.